The Impact of Knowledge Management on Employee Performance A Field Study on Sahara Bank – Tripoli City (Al-Farooq Journal of Sciences, 2026)
This study aimed to analyze the impact of knowledge management on improving employee performance at Al-Sahara Bank - Tripoli. The study considered knowledge management as the independent variable, while improving employee performance was the dependent variable. The study relied on a simple random sample, where the target sample size was 97 individuals. A questionnaire form was used as the main tool for collecting data related to the study variables. Ninety-six valid questionnaire forms were subjected to statistical analysis using the Statistical Package for Social Sciences (SPSS) software, after excluding one form due to incomplete responses. The study followed a descriptive-analytical approach in analyzing and interpreting the impact between its variables. The study reached several conclusions, most notably: the bank possesses a strong infrastructure that supports innovation and continuous improvement by encouraging new ideas and providing necessary resources. The study also reached several recommendations, most importantly: the need to work on documenting and measuring the impact of innovative ideas on institutional performance, while establishing a clear incentive system that recognizes employees' innovative contributions.
Keywords: Knowledge Management – Staff Performance – Financial Institution